Coming out with the Divinity of all closets! Gender, religion and sex-gender diversity - Vega-Dávila, Enrique (2023)
Intersectionality has made it possible to recognize and denounce many edges around the violence experienced by multiple corporalities. A variable in the middle of the political and cultural scene in the American continent is Christianity, which has played a vital role in the control of bodies and identities. In this sense, when addressing sex and gender diversities, it is also necessary to critically examine their role, their discourses and how they have affected bodies. The following presentation uses the methodological proposal of Liberation Theology (Boff, 2009), that is, using the three mediations: the socioanalytic related to the lives of people of sexual and gender diversity; hermeneutics, considering the way of reading Scripture recognized as sacred for Christianity and the proposal to come out of the closet; finally, the practice, related to some anthropo-theological proposals for the pastoral. The article also uses an autoethnographic perspective (Ellis et al., 2019) that dialogues with queer theoretical and theological positions. “Coming out” with the Divinity implies a political position that implies authenticity.